Perspektif Perilaku dalam Adopsi Sistem Akuntansi Berbasis Cloud - Luh Sintia Soniantari; Gusi Putu Lestara Permana (Universitas Prof.Hazairin,SH Bengkulu, 2025)
Purpose: This paper investigates the extent to which perceived usefulness, usability, and trust affect the acceptance of cloud-based accounting technologies among SMEs operating in Denpasar City. SMEs play an essential role in national economic growth. However, many still rely on conventional methods for accounting records. Cloud-based accounting emerges as a cloud-based tool for modernizing financial records, yet its adoption rate remains low. Methodology/approach: This study adopted a quantitative design, gathering responses from 120 individuals via standardized survey instruments. The collected data were analyzed through multiple linear regression in order to test the hypotheses formulated under the framework of the Technology Acceptance Model (TAM). Result/findings: The findings reveal that PU, PEOU, and trust all have a positive and significant effect on the adoption of cloud-based accounting systems. These results highlight that building user trust, alongside ensuring ease of use and clear benefits, is essential to promote adoption. Conclusion: This research provides valuable insights that support the formulation of effective strategies for technology providers to enhance user acceptance and provides valuable insights for future research on digital financial tools. Keywords: Cloud-based accounting, perceived usefulness, perceived ease of use, trust, TAM